2020
DOI: 10.1002/mnfr.202000003
|View full text |Cite
|
Sign up to set email alerts
|

[6]‐Gingerol Ameliorates ISO‐Induced Myocardial Fibrosis by Reducing Oxidative Stress, Inflammation, and Apoptosis through Inhibition of TLR4/MAPKs/NF‐κB Pathway

Abstract: Scope [6]‐Gingerol is one of the primary pungent constituents of ginger. While [6]‐gingerol has many pharmacological effects, its benefits for myocardial fibrosis, including its exact role and underlying mechanisms, remain largely unexplored. The present study is designed to characterize the cardio‐protective effects of [6]‐gingerol in myocardial fibrosis mice and possible underlying mechanisms. Methods and results Mice are subcutaneously injected with isoproterenol (ISO, 10 mg kg−1) and gavaged with [6]‐ginge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 70 publications
4
18
0
Order By: Relevance
“…A similar behavior was noted for taurolidine (Fink et al., 2018), which also mirrors the lack of oxidative stress observed in the current study (Figure 6). This is in congruence with the antioxidant activity of GNG observed in rodents (Han et al., 2020; Hegazy et al., 2016), but contradicts the oxidative damage seen in cancer cells (Lin et al., 2012; Yang et al., 2010). It seems likely that GNG may exhibit differential interaction dynamics with the antioxidant system in normal and cancer cells in both rodent and man.…”
Section: Discussionsupporting
confidence: 80%
“…A similar behavior was noted for taurolidine (Fink et al., 2018), which also mirrors the lack of oxidative stress observed in the current study (Figure 6). This is in congruence with the antioxidant activity of GNG observed in rodents (Han et al., 2020; Hegazy et al., 2016), but contradicts the oxidative damage seen in cancer cells (Lin et al., 2012; Yang et al., 2010). It seems likely that GNG may exhibit differential interaction dynamics with the antioxidant system in normal and cancer cells in both rodent and man.…”
Section: Discussionsupporting
confidence: 80%
“…Under normal physiological conditions, the synthesis and degradation of the extracellular matrix (ECM) in the normal heart maintains a dynamic balance ( Ma et al, 2018 ; Han et al, 2020 ). Previous study demonstrated that an imbalance between ECM synthesis and degradation may induce MF ( Zhang et al, 2017b ).…”
Section: Discussionmentioning
confidence: 99%
“…With the increase of extract concentration, the inhibition zone increased. When the concentration of the extract was 100 μ g/mL, Klebsiella pneumonia showed the highest susceptibility (29.04 ± 0.35 mm), followed by Pseudomonas aeruginosa , Escherichia coli , and Salmonella typhi , while Staphylococcus aureus had the least inhibition zone [ 33 ]. Different concentration of ZEE had different degrees of antibacterial effect, and the most antibacterial effect was at 75% ethanol solution.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%